Kajian Literasi Kesehatan serta Edukasi Prolanis sebagai Upaya Mewujudkan Lansia Sehat yang Mandiri, Aktif, dan Produktif - Sunardi, Kartika Setyaningsih; Noor, Ahmad Yani; Yuliasri, Tita Restu (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The aims of this community service were: (1) to understand how the elderly can search, understand, and apply the health information they obtained; (2) optimize how the elderly accessed health services; and (3) increase the knowledge and interest of the elderly in accessing prolanis at the nearest primary health services. Research Methodology: The service was located in two elderly integrated service posts or pos yandu lansia, pos yandu lansia Manggulan Village, and posyandu lansia Pikgondang Village. These two posyandu were in one district, namely District Condongcatur, Depok, Sleman, and the Special Region of Yogyakarta. The assessment of health literacy was carried out by interviewing the elderly using a health literacy questionnaire (HLS-EU-Q16), while the prolanis education activity was carried out in two sessions: a session of education and a session of direct counseling with the team. Results: The results of the activity show that the health literacy of the elderly is good enough even though they have a low educational background. The enthusiasm of the participants was very high in participating in a session of activities in the elderly posyandu. Limitations: The elderly who participated in the community service program were only those who regularly participated in posyandu activities, so it did not include all the elderly who live around the posyandu area. Contribution: (1) The team could make older posyandu activities more enjoyable so that other elderly people who have not participated become interested in attending; (2) increased the knowledge and interest of elderly people to visit health services to take prolanis; (3) even though the elderly's health literacy was good, the presence of the team made the elderly want to invite other elderly people to participate in posyandu lansia.